2020
DOI: 10.2478/hukin-2020-0031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inspiratory Muscle Training of Various Intensities on The Physical Performance of Long‐Distance Runners

Abstract: The aim of this study was to assess the efficacy of inspiratory muscle training (IMT) at different intensities on the pulmonary function and physiological adaptations of long-distance runners undergoing sports training. This study involved 25 long-distance runners. The subjects were randomly divided into three groups depending on the type of IMT applied: POWERbreathe device (group 1), Threshold IMT device (group 2), and a control group. The following lung variables were evaluated: vital capacity (VC), forced v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…This finding agrees with that reported by Najafi et al (2019) in youth soccer players, who, after a similar period of IMT, found no improvements in the analyzed spirometric variables. In contrast, other authors observed improved spirometric variables at rest in endurance runners with an IMT protocol of similar duration to the present study (Rozek-Piechura et al, 2020). Regarding the variables measured during the progressive incremental test, a significant difference in favor of the EXP group was observed in power associated with VO2max (pVO2max) and power associated with the VT1 threshold (pVT1) only.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…This finding agrees with that reported by Najafi et al (2019) in youth soccer players, who, after a similar period of IMT, found no improvements in the analyzed spirometric variables. In contrast, other authors observed improved spirometric variables at rest in endurance runners with an IMT protocol of similar duration to the present study (Rozek-Piechura et al, 2020). Regarding the variables measured during the progressive incremental test, a significant difference in favor of the EXP group was observed in power associated with VO2max (pVO2max) and power associated with the VT1 threshold (pVT1) only.…”
Section: Discussioncontrasting
confidence: 81%
“…A performance improvement was also observed in male rowers after four weeks of IMT, which was not verified when the expiratory musculature was trained during the same period ( Griffiths and McConnell, 2007 ). In elite endurance runners, eight weeks of IMT increased relative VO 2max and decreased post-training blood lactate values ( Rozek-Piechura et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies (49) deal with sports performance monitoring. Thus, motor qualities are constantly analyzed by many sportsmen, specialists, and researchers (21 papers).…”
Section: Number Of Articles Published By Training Segmentmentioning
confidence: 99%
“…IMT influence on pulmonary function in disabled swimmers showed a significant increase in ventilatory function and respiratory muscle strength (Okrzymowska et al, 2019). Rożek-Piechura et al (2020) reported a significant improvement in most of the lung ventilation variables and respiratory muscle strength in longdistance runners after 8 weeks of IMT using a POWERbreathe device; however, using a Threshold device, only the vital capacity improved significantly.…”
Section: Introductionmentioning
confidence: 99%